2020
DOI: 10.5812/pedinfect.92752
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Predictors of Severity of Pediatric Scrub Typhus in a Tertiary Level Hospital in South India

Abstract: Background: Scrub typhus, a zoonosis caused by bacteria Orientia tsutsugamushi is associated with varying clinical features and significant mortality due to complication in view of ineffective treatment. Objectives: This study was undertaken to identify the factors for predicting severity in scrub typhus. Methods: This retrospective study was conducted at a tertiary care teaching hospital between January 2015 to October 2016. All children younger than 18 years of age admitted with a history of fever for more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…About a third of the scrub typhus cases requiring hospitalization have multi-organ dysfunction with pulmonary, hepatic, cardiac, neurological, or renal complications leading to high fatality rates [6,10]. Studies from India reveal that the case fatality rate (CFR) of scrub typhus ranges from 1.3% to 33.5% depending on the organ involvement and complications present [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…About a third of the scrub typhus cases requiring hospitalization have multi-organ dysfunction with pulmonary, hepatic, cardiac, neurological, or renal complications leading to high fatality rates [6,10]. Studies from India reveal that the case fatality rate (CFR) of scrub typhus ranges from 1.3% to 33.5% depending on the organ involvement and complications present [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5,10,16 Clinically significant icterus was present in only 7.8% cases with average bilirubin level 0.4±0.13 mg/dL in our study. 11 Interestingly, some pediatric studies have reported jaundice in as high as 30.7% cases. 10,14 Although very common in acute viral hepatitis, jaundice is not a common finding in scrub typhus, hence appropriately termed as anicteric hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Both these findings in absence of eschar have been studied as disease severity indicators. 9,11 Despite having such importance from clinical and prognostic point of views, there are few studies concentrating upon hepatic profile of scrub typhus, especially in pediatric population. 12 Majority of such studies are based on adult population and pediatric data on scrub typhus associated hepatic injury is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Severe hypoalbuminemia was considered if the serum level was <2.5 gm/dl. 3 Prolonged international normalized ratio (INR) was defined as INR>1.5.…”
mentioning
confidence: 99%